AKHLAK DALAM PERSPEKTIF AL-ISLAM DALAM HADIS - St. Nurfadillah. A; A. Dwi Mulyana; Zubair; Andi Farras Abbiyu; Dahlan Lama Bawa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Morality is the core of Islamic teachings and the main indicator of the quality of a Muslim's faith. The Prophet Muhammad SAW was sent to perfect human morality, as emphasized in various hadiths. This article aims to analyze the concept of morality from an Islamic perspective based on the hadiths of the Prophet Muhammad SAW and its relevance in modern society. This research uses a qualitative method with a literature study approach to the hadiths of the Prophet and classical and contemporary Islamic literature. The results of the study show that morality in Islam encompasses three main dimensions, namely morality towards Allah SWT., morality towards oneself, and morality towards fellow human beings. Values such as sincerity, patience, gratitude, honesty, trustworthiness, justice, compassion, and guarding one's tongue form the foundation for the development of faith and civilization. Thus, ethics not only function as individual ethics but also as the main pillars for the formation of a civilized and just society.